Examine the Effects of Adding Low-Dose Ketomine to Tramadol in Order to Prevent Shivering during Spinal Anesthesia - Muhammad Zia, Muhammad Muazzam Butt, Hafiz Muhammad Waseem Yaseen, Abdul Bary, Sahito Khan Rind, Rakhshinda Younus, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose was to evaluate the effects of adding a barely amount of ketamine to tramadol to avoid shivering when under spinal anesthesia. Study Design: Retrospective Study. Place and Duration: Department of Anesthesia & ICU, Madina Teaching Hospital/Punjab Medical College Faisalabad during April 2022 to February 2023. Methods: Total 140 patients of both genders undergoing inguinal hernia were included in this study. Patients were divided equally into two groups. Group I received low dose ketamine 0.25 mg/kg (K) into tramadol in 70 case and 70 cases of group II received tramadol 0.5 mg/kg (T) alone. The efficiency of both groups' post-treatment shivering control was compared. The SPSS 26.0 version was utilized to evaluate all of the data. Results: In comparison to tramadol alone, which caused shivering in 33 (47.1%) of the patients, we determined that a low dose of ketamine added to tramadol effectively reduced shivering in 32 (31.4%) of the instances (p value <0.003). Conclusion: In this study, we came to the conclusion that treating patients having surgery with a low dose of ketamine added to tramadol under spinal anesthetic reduces shivering more effectively and usefully than tramadol alone. Keywords: Ketamine, Shivering, Tramadol, Spinal Anesthesia